Coevolutionary legacies for plant decomposition. (January 2023) - Cornelissen, J. Hans C.; Cornwell, William K.; Freschet, Grégoire T.; Weedon, James T.; Berg, Matty P.; Zanne, Amy E.
Abstract : Coevolution has driven speciation and evolutionary novelty in functional traits across the Tree of Life. Classic coevolutionary syndromes such as plant–pollinator, plant–herbivore, and host–parasite have focused strongly on the fitness consequences during the lifetime of the interacting partners. Less is known about the consequences of coevolved traits for ecosystem-level processes, in particular their 'afterlife' legacies for litter decomposition, nutrient cycling, and the functional ecology of decomposers. We review the mechanisms by which traits resulting from coevolution between plants and their consumers, microbial symbionts, or humans, and between microbial decomposers and invertebrates, drive plant litter decomposition pathways and rates. This supports the idea that much of current global variation in the decomposition of plant material is a legacy of coevolution. Highlights: Plant litter decomposition adds a different process and ecological context to the coevolution literature, which has thus far focused on the ecology of symbionts during their lifetimes. This context integrates the literature on how arms races between plants and their consumers (herbivores, pathogens) or mutualists (nitrogen-fixing bacteria, mycorrhizal fungi) drive the quality of plant tissue, with an important legacy for litter decomposability. We know little about recent coevolutionary decomposition legacies involving plant domestication by humans via farming, plant breeding, and modified landscapes with feedback to evolution of human brain, digestion, and dentition. How myriad coevolutionary links between invertebrates and microbial decomposers affect global carbon cycling needs further investigation. Overall, plant decomposition rates are largely the legacy of wide-ranging coevolutionary relationships.